METHODOLOGICAL BASE FOR TRANSFORMANTS REPRESENTATION IN NONEQUILIBRIUM POSITIONAL UNEVEN-DIAGONAL SPACE - Barannik, V. V.; Krasnorutskyi А. А. (Science-based technologies, 2015)
It is shown the relevance of development of technologies of lowering of intensity of a video stream and code representation of a basic frame as its key component. It is explained the basic aspects of creation of a method of formation of nonequilibrium positional uneven-diagonal basis that based on detection of dynamic ranges for separate uneven diagonals depending on their index number and the zigzag direction. It is developed the model of an assessment of informtiveness of a transformant taking into account that the transformant of discrete cosine transformation, is considered on uneven diagonal structure, and represents combinatorial object, namely reversion with reiteration on which dynamic ranges of elements restrictions are imposed. It is grounded that in the conditions of existence of a tendency in change of properties of a transformants in the diagonal direction for a eneven-diagonal method of detection of dynamic ranges is providing the potential of rather additional elimination of structural redundance in basic frames.